(Information letter) Мethod of long-term storage of museum strains of microorganisms - Minukhin, Valeriy; Sklyar, Nadiya; Peretyatko, Olena; Yagniuk, Yuliia; Krestetska , Svitlana; Bolshakova, Galina (Annals of Mechnikov's Institute, 2023)
The мethod of long-term storage of museum strains in collections is proposed. It consists in the preservation of microorganisms by freezing cultures at a temperature of -20 ºС in a nutrient environment with glycerin. The use of glycerol as a cryoprotectant is due to its ability to increase the viscosity of the medium, cause moderate dehydration of cells during cooling, inhibit the formation of ice crystal nuclei, thereby increasing the resistance of plasma membranes to low temperatures and protecting microbial cells from the harmful effects of freezing. The proposed мethod will make it possible to optimize the maintenance of microbial collections which are necessary for the effective operation of laboratories/departments of microbiological profile of health care institutions, scientific, scientific research, scientific and industrial institutions. Key words: museum strains of microorganisms, long-term storage, nutrient medium with glycerin, freezing.